Correcting the NLRP3 inflammasome deficiency in macrophages from autoimmune NZB mice with exon skipping antisense oligonucleotides. Issue 5 (2nd February 2016) - Thygesen, Sara J; Sester, David P; Cridland, Simon O; Wilton, Steve D; Stacey, Katryn J
Abstract : Inflammasomes are molecular complexes activated by infection and cellular stress, leading to caspase‐1 activation and subsequent interleukin‐1β (IL‐1β) processing and cell death. The autoimmune NZB mouse strain does not express NLRP3, a key inflammasome initiator mediating responses to a wide variety of stimuli including endogenous danger signals, environmental irritants and a range of bacterial, fungal and viral pathogens. We have previously identified an intronic point mutation in the Nlrp3 gene from NZB mice that generates a splice acceptor site. This leads to inclusion of a pseudoexon that introduces an early termination codon and is proposed to be the cause of NLRP3 inflammasome deficiency in NZB cells. Here we have used exon skipping antisense oligonucleotides (AONs) to prevent aberrant splicing of Nlrp3 in NZB macrophages, and this restored both NLRP3 protein expression and NLRP3 inflammasome activity. Thus, the single point mutation leading to aberrant splicing is the sole cause of NLRP3 inflammasome deficiency in NZB macrophages. The NZB mouse provides a model for addressing a splicing defect in macrophages and could be used to further investigate AON design and delivery of AONs to macrophages in vivo .